Analyses of anomalous lensing events detected from the UKIRT microlensing survey - Han C; Zang W; Udalski A; Lee C-U; Bond IA; Wen Y; Ma B; Albrow MD; Chung S-J; Gould A; Hwang K-H; Jung YK; et al. (EDP Sciences, 2025)
Aims. The United Kingdom Infrared Telescope (UKIRT) microlensing survey was conducted over four years, from 2016 to 2019, with the goal of serving as a precursor to future near-infrared microlensing surveys. Focusing on stars in the Galactic center and utilizing near-infrared passbands, the survey identified approximately one thousand microlensing events, 27 of which displayed anomalies in their light curves. This paper presents an analysis of these anomalous events, aiming to uncover the underlying causes of the observed anomalies. Methods. The events were analyzed under various configurations, considering the potential binarity of both the lens and the source. For 11 events that were additionally observed by other optical microlensing surveys, including those conducted by the OGLE, KMTNet, and MOA collaborations, we incorporated their data into our analysis. Results. Among the reported anomalous events, we revealed the nature of 24 events except for three events, in which one was likely to be a transient variable, and two were difficult to accurately characterize their nature due to the limitations of the available data. We confirmed the binary lens nature of the anomalies in 22 events. Among these, we verified the earlier discovery that the companion in the binary lens system UKIRT11L is a planetary object. Accurately describing the anomaly in UKIRT21 required a model that accounted for the binarity of both the lens and the source. For two events UKIRT01 and UKIRT17, the anomalies could be interpreted using either a binary-source or a binary-lens model. For the UKIRT05, it was found that accounting for higher-order effects induced by the orbit al motions of both Earth and the binary lens was crucial. With the measured microlensing parallax togeter with the angular Einstein radius, the component masses of the UKIRT05 binary lens were determined to be M1 = (1.05 ± 0.20) M⊙, M2 = (0.36 ± 0.07) M⊙, and the distance to the lens was found to be DL = (3.11 ± 0.40) kpc.
Keywords: gravitational lensing: micro